NOTES AND CORRESPONDENCE. - Levi, Charles; Albright, Charlotte; Omry, Keren; Vint, Sherryl (Science Fiction Studies, 2019)
A biography of Flossie E. Hardart, a science fiction writer is presented. Topics include the visibility of her science fiction works in the 1930s and early 1940s discussing the number of women authors in science fiction during that time, views of Sarah Lefanu that women authors assumed a male voice and non-gender specific names to avoid prejudice on the part of editors and readers, and questioning of her question her identity and authorship due to one of her nonfiction article.